Conversion of Traditional Journalism in the Age of Information: Data Journalism - ASLAN, ALAATTİN; BAYRAKCI, SERKAN (MARMARA UNIV, FAC COMMUNICATION, 2016)
The changes in technology and the emergence of information revolution as a result of these changes lead to differences in journalists' methods of getting news. These developments in computer and internet area have affected the profession of journalism and this situation led to the emergence of concept of data journalism. Data journalism reflects a system in which open data and online reporting are used for creating the story which constitutes the essence of journalism. The changes in both news distribution environment and news consumption habits have directed news corporations and journalists to a new area. This environment is called internet - a free and unlimited source- in which unstructured data are abundantly available. In today's environment where almost everything is expressed numerically, in other words digitized; internet has become the most significant channel for data journalism. For the data journalism to work efficiently, data should be clear, analyzable and be in a format which is proper for turning into a story. Therefore, the first task of data journalists appears as purifying data from redundancy and combining them by using multiple methods in order to create the story. This study aims to clarify and explain the concept of data journalism -a new aspect of journalism and its processes. As a research method, descriptive research model has been used in the study and data journalism examples have been evaluated. By means of this evaluation, a discussion about transforming of traditional journalism into data journalism and the effect of data journalism concept on understanding of new aspect of journalism has been conducted. As a result, conveying the news by making a story of it based on data is regarded as a new movement. Besides, making a story out of news clarifies a serious example related to the reliability of news and how open source data are conveyed to the public. It is understood well that this new understanding of journalism-which conveys consistent information to the public by using information systems- will lead to a dramatic change in understanding of traditional journalism.
Keywords: Open Data; Data Manipulation; Data Journalism; Big Data